1988
DOI: 10.1161/01.cir.78.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Morning increase in platelet aggregability. Association with assumption of the upright posture.

Abstract: The frequencies of onset of myocardial infarction and sudden cardiac death are increased between 6 AM and 12 noon. Platelet aggregability, which may play a role in the cause of these disorders, has been observed to increase after the normal morning activities of awakening, arising, and ambulating. To determine which morning activity or activities are responsible for this aggregability increase, we measured platelet aggregation in 16 normal subjects on a control day of delayed arising (i.e., subjects remained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(74 citation statements)
references
References 18 publications
4
69
1
Order By: Relevance
“…Other changes noted in the morning, especially with assumption of the upright posture, include increased heart rate, sympathetic tone, renin activity, and plasma concentrations of cortisol, epinephrine, norepinephrine, and angiotensin II. 9,30,32,38,39 Sympathetic activity may further enhance platelet aggregation, 40 and cortisol may increase sensitivity of the coronary arteries to the vasoconstrictor effects of catecholamines. 41,42 Increased blood viscosity and platelet aggregability in the absence of a compensatory increase in circulating tissue-type plasminogen activator activity results in an environment of relative hypercoagulability.…”
Section: Resultsmentioning
confidence: 99%
“…Other changes noted in the morning, especially with assumption of the upright posture, include increased heart rate, sympathetic tone, renin activity, and plasma concentrations of cortisol, epinephrine, norepinephrine, and angiotensin II. 9,30,32,38,39 Sympathetic activity may further enhance platelet aggregation, 40 and cortisol may increase sensitivity of the coronary arteries to the vasoconstrictor effects of catecholamines. 41,42 Increased blood viscosity and platelet aggregability in the absence of a compensatory increase in circulating tissue-type plasminogen activator activity results in an environment of relative hypercoagulability.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22] The increase in platelet aggregability appears to be related to physiologic changes occurring during the time of awakening and getting up. 23 The importance of platelet characteristics is underlined by large clinical trials that have shown that24-27 antiplatelet therapy reduces myocardial infarction.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] Analysis of this circadian variations is important to clarify the triggering mechanisms of AMI.Although the precise underlying mechanisms of the circadian variation of AMI are still unclear, the morning peak appears to be associated with surges of blood pressure, 11-13 neurohumoral factors 14,15 and platelet aggregability; [16][17][18] that is, it appears to be associated with an inherent biologic rhythm. However, the second peak in the evening is more associated with socioeconomic factors, such as the timing of the evening meal, 19 mental stress 20-22 and overtime work, 23 but it is unclear which population is more susceptible to the morning surge or to the nighttime socioeconomic factors.…”
mentioning
confidence: 99%